Multiparametric magnetic resonance imaging ultrasound-guided fusion biopsy during active surveillance: A single-centre study. Issue 3 (2nd July 2020) - Röthlin, Kilian; Zamboni, Stefania; Moschini, Marco; Stucki, Patrick; Afferi, Luca; Baumeister, Philipp; Mattei, Agostino
ABSTRACT: Objective: To analyse the role of multiparametric magnetic resonance imaging (mpMRI) ultrasound (US)-guided fusion biopsy (FB) in patients with low-risk prostate cancer (PCa) under active surveillance (AS). Patients and methods: Our retrospective study included 47 patients under AS who consecutively underwent both FB and standard biopsy (SB), from May 2015 until November 2017. We defined FB as a transrectal US-guided biopsy based on mpMRI. The primary endpoint was to assess the rate of concordance between FB and SB in terms of diagnostic yield, as well as the rate of Gleason Score upgrading/downgrading between the two techniques. Cohen's kappa coefficient (κ) was applied to test the concordance between FB and SB. Results: The median (interquartile range [IQR]) follow-up was 20 (13–37) months. The median (IQR) number of cores taken was 13 (12–14) at SB and 4 (4–6) at FB. Overall, FB missed 12/47 (26%) PCa diagnoses compared to SB. There was concordance between SB and FB in 64% of the patients. The κ showed a perfect agreement between SB and FB for the detection of PCa with Gleason Score 4 + 4 and a weak concordance for negative biopsies ( κ : 0.46) and for PCa with a Gleason Score 4 + 3 ( κ : 0.54). There was Gleason Score upgrading at FB in two of 47 (4%) patients, whereas there was downgrading in three of 47 (6%) patients. Conclusion: In our present study, FB showed no superiority over SB for the detection of PCa. On the contrary, FB had a high rate of missed PCa compared to SB. Further studies are required to ascertain the role of FB in AS. Abbreviations: AS: active surveillance; FB: fusion biopsy; IL: index lesion; IQR: interquartile range; mpMRI: multiparametric MRI; (cs)PCa: (clinically significant) prostate cancer; PI-RADS: Prostate Imaging-Reporting and Data System; PRIAS: Prostate Cancer Research International Active Surveillance; ROI: region of interest; SB: standard biopsy